KUALITAS PELAYANAN AKADEMIK DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS MADAKO KABUPATEN TOLITOLI PROVINSI SULAWESI TENGAH - Sawir, Mohammad (Katalogis, 2017)
This research aims at determining the quality of academic services at the Faculty of Social and Political Sciences of Madako University. This research uses the theory of service quality proposed by Zenthaml Parasuraman. Type of research is qualitative. The informants of this research consist leccturers, teaching staff, students and alumni who are determined purposively, with data collection methods consisted of observation, interviews and documentation. Data analysis techniques include data reduction, data verification and drawing conclusions. Research results indicate that the quality of academic services in the context of teaching and learning process in Faculty of Social and Political Sciences of Madako University is not qualified yet. This is evidenced by five dimensions used as a benchmark; barely four dimensions go well namely the dimensions of Reliability, Responsiveness, Assurance and Empathy. While the dimension of tangible is inadequate therefore the academic services are not running properly. This is due to the unavailability of sufficient facilities that can support the lecturing process, such as unavailability of representative study room, unavailability of lecture rooms, unavailability of parking space, unavailability of worship facilities and library facilities that are not functioning.